Landscape fragmentation, severe drought, and the new Amazon forest fire regime - Alencar, Ane A; Brando, Paulo M; Asner, Gregory P; Putz, Francis E (Ecological applications, 2015)
Changes in weather and land use are transforming the spatial and temporal characteristics of fire regimes in Amazonia, with important effects on the functioning of dense (i.e., closed-canopy), open-canopy, and transitional forests across the Basin. To quantify, document, and describe the characteristics and recent changes in forest fire regimes, we sampled 6 million ha of these three representative forests of the eastern and southern edges of the Amazon using 24 years (1983-2007) of satellite-derived annual forest fire scar maps and 16 years of monthly hot pixel information (1992-2007). Our results reveal that changes in forest fire regime properties differentially affected these three forest types in terms of area burned and fire scar size, frequency, and seasonality. During the study period, forest fires burned 15% (0.3 million ha), 44% (1 million ha), and 46% (0.6 million ha) of dense, open, and transitional forests, respectively. Total forest area burned and fire scar size tended to increase over time (even in years of average rainfall in open canopy and transitional forests). In dense forests, most of the temporal variability in fire regime properties was linked to El Nino Southern Oscillation (ENSO)-related droughts. Compared with dense forests, transitional and open forests experienced fires twice as frequently, with at least 20% of these forests' areas burning two or more times during the 24-year study period. Open and transitional forests also experienced higher deforestation rates than dense forests. During drier years, the end of the dry season was delayed by about a month, which resulted in larger burn scars and increases in overall area burned later in the season. These observations suggest that climate-mediated forest flammability is enhanced by landscape fragmentation caused by deforestation, as observed for open and transitional forests in the Eastern portion of the Amazon Basin.